Antibody, cell‐mediated response and infection susceptibility in allogeneic hematopoietic stem cell recipients after COVID‐19 mRNA vaccination. Issue 2 (7th February 2023) - Pizzano, Umberto; Facchin, Gabriele; Marcon, Chiara; Fabris, Martina; Battista, Marta Lisa; Cerno, Michela; Geromin, Antonella; Pucillo, Martina; Petruzzellis, Giuseppe; Vianello, Giampaolo; Battaglia, Giulia; Peressutti, Roberto; et al.
Abstract: Background: Patients undergoing allogeneic stem‐cell transplantation (allo‐SCT) have reduced responses to vaccines due to immunosuppressive status linked to GvHD prophylaxis and treatment. In our study, we compared humoral responses to anti‐SARS‐CoV‐2 mRNA vaccine, and infection onset, according to patients and transplant features; we also evaluated cellular response in patients without seroconversion. Methods: We tested antibodies titer after second and third vaccine doses. Antibodies were detected through an immune‐enzymatic assay. In a patients' subgroup without seroconversion, we tested cell‐mediated responses evaluating interferon‐gamma release by T‐lymphocytes exposed to virus spike protein. Results: Seroconversion rate increased from 66% at 30 days to 81% at 90 days after the second dose; it was 97% at 150 days after the third dose. We found a significant association between seroconversion after the second dose and two variables: shorter interval between allo‐SCT and vaccination; ongoing immunosuppression. Twelve of 19 patients (63%) without antibodies after the second dose did not show cellular responses. Nineteen percent of patients developed SARS‐CoV‐2 infection after the third dose, with favorable outcome in all cases. Patients within 12 months after allo‐SCT showed a significantly higher infection risk. Conclusions: Our study suggests that an interval shorter than 12 months between allo‐SCT and first vaccine dose and/or ongoing immunosuppression were associated with humoral and cellular response deficiency after two doses. Third dose induced an increased and sustained humoral response in the majority of patients. However, patients within 1 year after allo‐SCT remained at higher infection risk and may be candidate for prophylaxis with anti‐SARS‐CoV‐2 monoclonal antibodies. Abstract :